Co-Relation between Work Ability and Severity of Musculoskeletal Discomfort in Middle Aged Persons - Drashti H Trivedi; Megha S Sheth (National Journal of Community Medicine, 2018)
Introduction: Work ability is an acquired or natural capacity that enables an individual to perform a particular job or task successfully. Work ability index is a tool to record the working ability of employees. The objective of the study was to correlate work ability with severity of musculoskeletal disorders in middle aged person.